OP0274 Fibromyalgia in real life: a national french web-based survey in 4516 patients. (15th June 2017) - Laroche, F; Guérin, J; Azoulay, D; Coste, J; Perrot, S
Abstract : Background: Fibromyalgia (FM) is the most frequent widespread chronic pain disorder (1, 6% of the French population) (1). The medical and socioeconomic burden is high and severity depends on medical status and symptoms as defined by the OMERACT criteria (2). Most of the studies are performed in specialized centers, recruiting the most severe patients, but very few data exist on its real impact on daily life. Objectives: The aims were to collect demographic data, symptoms, function, diagnosis, management strategies and health care utilization in real life, in a large population, and to determine clusters of patients. Methods: A large internet-based national survey of people suffering from FM was developed by a national patient association (Fibromyalgie-SOS Association) on their website, in France in 2014. The survey included 103 qualitative and quantitative questions that were developed by 3 medical experts (including rheumatologists) and patients. Results: The questionnaire was completed by 4516 people. Respondents were predominantly middleaged (48 yrs) females (93%), most of whom had FM symptoms duration for 12 years and a diagnosis for 5 years. Diagnosis was made by a rheumatologist in 54% of the cases. The symptoms were concordant with the OMERACT domains (chronic pain, fatigue stiffness and other FM-associated symptoms) as previously published by Bennett in 2007 (3). The mean FIQ (Fibromyalgia Impact Questionnaire) score was 51 (0–100). 55% were currently working but 65% of them have been on sick leave in the 12 previous months. FIQ was mostly impacted by injustice feeling (+4.5), part time job (+2.4) and low income - less than 1000 euros monthly (+2.3) (linear regression). Somatic comorbidities were mostly osteoarthritis (49%). Psychological comorbidities were injustice feeling (77%), cognitive symptoms (62%), anxiety (52%) and depression (48%). Initiating factors were reported by 73% of them: physical (50%) and/or psychological (76%). Aggravating factors included excess of activities, conflicts, traumatism and displacement. Treatments were provided by general practitioner (85%), physiotherapist (63%), rheumatologist (54%) and osteopathic manual practitioner (41%). Treatment was prescribed in 76.6% of the patients, including paracetamol alone (51.4%), paracetamol and weak opioids (64%), strong opioids (20.1%), antidepressants (81.5%), antiepileptic agents (54.5%), nonsteroidals NSAIDs (53.8%), anxiolytics (52.4%) and steroids (12.8%). Conclusions: This unique descriptive survey in a large population provides data on symptoms, emotional distress, prescribing habits and impact of FM on daily life and work. Results show that FM is altered by emotional (including injustice feeling) and socio-economic factors. References: Perrot S, Vicaut E, Servant D, Ravaud P. Prevalence of fibromyalgia in France: a multi-step study research combining national screening and clinical confirmation: The DEFI study (Determination of Epidemiology of Fibromyalgia). BMC Musculoskeletal Disorders 2011; 12:224. Mease P, Clauw D, Arnold L. and the OMERACT Fibromyalgia Working Group. The Journal of Rheumatology, 2011; 38: 1487–95. Bennett R. Jones J, Turk D, Russell I, Matallana L. An internet survey of 2, 596 people with fibromyalgia. BMC Musculoskeletal Disorders 2007, 8:27: 1–11. Disclosure of Interest: None declared